Peningkatan Pengetahuan Petani Sekolah Lapang Budidaya Kopi di Kabupaten Serang Provinsi Banten - Okta Wulandono (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2021)
Coffee is one of the leading plantation commodities in Banten Province. There are challenges in developing this commodity. But there are also many opportunities and potentials from coffee cultivation. Various programs are implemented to increase production, productivity, and post-harvest development of coffee commodities, one of which is field schools. In 2021, a coffee cultivation field school be held in Cinangka District, Serang Regency, Banten Province. This study uses data from the pre-test and post-test results of field school teaching materials. The purpose of this study is to see the level of effectiveness of the field school. The purpose of this research is also to see the change of farmers' knowledge, before and after the program. This study uses the category of knowledge level analysis, Shapiro Wilk normality test, paired t-test, and analysis of the level of effectiveness. The results showed that the field school was able to change the knowledge level of farmers from the medium category (33.67%) to the high knowledge level category (70.50%). Based on the Shapiro Wilk normality test, the research databases were normally distributed in all pre-test post-test learning materials given. The calculation of paired t-test shows that there are differences in the level of knowledge of farmers before and after the field school, with the average t value for all materials at 24.510 and t table 2.045. The overall implementation of the field school shows a fairly effective level of effectiveness.